Deberes funcionales de la policía ante la violencia familiar - Cuevas-Montes, Franklin (Instituto Universitario de Innovación Ciencia y Tecnología Inudi Perú, 2022)
This book is an adaptation of an investigation presented to the Universidad Nacional Hermilio Valdizán, whose objective was to determine the relationship between the omission of the functional duties of the police and family violence. To do this, we study the relationship between physical and psychological family violence with the functional duties of the police. The technique used is the survey, applying an instrument to women affected by family violence in the city of Huancavelica, with an estimated population of twenty affected per month on average. The results obtained show a significant relationship of 0.975. In conclusion, we can say that there is an omission of the functional duties of the police in the face of complaints of physical and psychological violence suffered by women in the city of Huancavelica.